Pengembangan Konten Video Pembelajaran Instalasi Penerangan Listrik di SMKN 1 Tumpaan - Josua Moonik; Benyamin Tampang; Agustinus Takaradase; Ridwan Ridwan; I Gede Budi Mahendra (Department of Electrical Engineering Education, Faculty of Engineering, State University of Manado, 2022)
This study aims to develop a learning video about electric lighting installations for class XI students. The research method used is the development method, better known as the research and development (R&D) ADDIE model. This study consists of five steps, namely: (1) analysis, (2) design, (3) development, (4) implementation, and (5) evaluation (evaluation). After testing media experts and material experts and being revised, then implemented in class XI TITL SMK Negeri 1, Tumpaan obtained learning outcomes with an average value of 81.6 in the